Measurement of the CKM angle γ using B 0 → DK *0 with D → K 0S π + π − decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; et al. (Journal of high energy physics, 2016)
A model-dependent amplitude analysis of the decay B0 → D(KS0π+π−)K∗ 0 is performed using proton-proton collision data corresponding to an integrated luminosity of 3.0 fb−1, recorded at s=7$$ \sqrt{s}=7 $$and 8 TeV by the LHCb experiment. The CP violation observables x± and y±, sensitive to the CKM angle γ, are measured to bex−=−0.15±0.14±0.03±0.01,y−=0.25±0.15±0.06±0.01,x+=0.05±0.24±0.04±0.01,y+=−0.65−0.23+0.24±0.08±0.01,$$ \begin{array}{l}{x}_{-}=-0.15\pm 0.14\pm 0.03\pm 0.01,\hfill \\ {}{y}_{-}=0.25\pm 0.15\pm 0.06\pm 0.01,\hfill \\ {}{x}_{+}=0.05\pm 0.24\pm 0.04\pm 0.01,\hfill \\ {}{y}_{+}=-{0.65}_{-0.23}^{+0.24}\pm 0.08\pm 0.01,\hfill \end{array} $$where the first uncertainties are statistical, the second systematic and the third arise from the uncertainty on the D → KS0π+π− amplitude model. These are the most precise measurements of these observables. They correspond to γ = (80− 22+ 21)° and rB0=0.39±0.13$$ {r}_{B^0}=0.39\pm 0.13 $$, where rB0$$ {r}_{B^0} $$is the magnitude of the ratio of the suppressed and favoured B0 → DK+π− decay amplitudes, in a Kπ mass region of ±50 MeV around the K*(892)0 mass and for an absolute value of the cosine of the K*0 decay angle larger than 0.4.
*The LHCb collaboration: R. Aaij, P. D'Argent, S. Bachmann, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, S. Esen, D. Gerick, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kecke, M. Kolpin, K. Kreplin, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Stahl, U. Uwer, M. Vesterinen, A. Zhelezov [und sehr viele weitere Personen]
Im Titel sind die Zeichen "*", "+" und "-" hochgestellt
Im Titel ist die Zahl 0 hochgestellt
Im Titel ist der Buchstabe s tiefgestellt
Gesehen am 02.07.2020